2022
DOI: 10.1186/s13104-022-05910-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estrogen on brown adipose tissue activity in male rats

Abstract: Objective Centrally administered estrogen can increase sympathetic nerve activity to brown adipose tissue, resulting in thermogenesis. The central thermogenic effects of estrogen have not been investigated in males. Therefore, this study sought to investigate the effects of peripherally and centrally administered estrogen on thermogenesis, heart rate and mean arterial pressure in male rats. Thermogenesis was assessed by monitoring brown adipose tissue temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…On the other hand, even considering the sex differences in Esr1 expression levels, the absence of an upregulation in DNL-related gene expression in male BAT explants upon direct E2 supplementation suggests that the estrogen-DNL regulatory system itself does not exist in male BAT. The previous report of no enhancement in BAT thermogenesis in male rats following peripheral estrogen administration 43 aligns with our results of the ex vivo experiment. In addition, it has been reported that male-to-female transsexuals undergoing estrogen replacement therapy exhibit a tendency toward obesity.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, even considering the sex differences in Esr1 expression levels, the absence of an upregulation in DNL-related gene expression in male BAT explants upon direct E2 supplementation suggests that the estrogen-DNL regulatory system itself does not exist in male BAT. The previous report of no enhancement in BAT thermogenesis in male rats following peripheral estrogen administration 43 aligns with our results of the ex vivo experiment. In addition, it has been reported that male-to-female transsexuals undergoing estrogen replacement therapy exhibit a tendency toward obesity.…”
Section: Discussionsupporting
confidence: 92%
“…In our KEGG results of the upregulated genes, the terms of steroid hormone biosynthesis, ovarian steroidogenesis and steroid biosynthesis are significantly enriched that directly related to steroid synthesis process; in addition, the thermogenesis and oxidative phosphorylation pathways are also significantly enriched, which may be related to steroid metabolism and oestrogen production. Thermogenesis is essential for warm‐blooded animals to ensure normal cellular and physiological function under conditions of environmental challenge, and oestrogen can increase sympathetic nerve activity in brown adipose tissue, resulting in thermogenesis (Martinez de Morentin et al., 2014; Sievers et al., 2022; Steiner & Berry, 2022). Oestrogen‐related receptor α regulates genes involved in fatty acid oxidation and oxidative phosphorylation in muscle (Kitamura et al., 2020), and the increase in oxidative stress inhibits mitochondrial oxidative phosphorylation and induces follicular apoptosis (Guo et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The ovary is a crucial reproductive organ responsible for oogenesis and hormone secretion in mammals (Smith et al, 2014). In equine foetuses, sexual differentiation occurs between 39 and 45 days of pregnancy (Barreto et al, 2018;Walt et al, 1979).…”
Section: Introductionmentioning
confidence: 99%